2014
DOI: 10.3844/jcssp.2014.54.65
|View full text |Cite
|
Sign up to set email alerts
|

Optimization Model of Selective Cutting for Timber Harvest Planning Based on a Simulated Annealing Approach

Abstract: An optimization model for Timber Harvest Planning (THP) is used to form harvest areas with the objective of maximizing the tree harvest volume subject to harvest regulations. Most optimization models for THP currently in use are based on clear cutting and restricted to adjacency constraints to prevent the creation of large clear-cut openings in the forest. However, an optimization model based on selective cuttingthe cutting technique utilized in tropical countries-has rarely been described in the literature. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Our model assumed that the forest owner's decision to maximize utility determines the optimal harvest strategy through their consumption levels and the constraint is the sum of the total consumption which cannot exceed the total profit generated from forestry. Dissimilar to other studies using LP models [13], this study did not set the ending age constraint to improve the current unbalanced forest age structure in the ROK. Instead, this study showed that the unbalanced age structure might be improved through the harvest prescription derived from the utility model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our model assumed that the forest owner's decision to maximize utility determines the optimal harvest strategy through their consumption levels and the constraint is the sum of the total consumption which cannot exceed the total profit generated from forestry. Dissimilar to other studies using LP models [13], this study did not set the ending age constraint to improve the current unbalanced forest age structure in the ROK. Instead, this study showed that the unbalanced age structure might be improved through the harvest prescription derived from the utility model.…”
Section: Discussionmentioning
confidence: 99%
“…They also formulated the Economic Harvest Optimization (ECHO) model as a quadratic objective version. Abdullah et al [13] developed an optimization model for timber harvesting planning based on the selective cutting technique. Their study subjected a maximum number of trees to be harvested and a minimum number of trees to be damaged during each planning period.…”
Section: Introductionmentioning
confidence: 99%